Enhancing Visit Intention through Virtual Cultural Tourism: The Roles of Interactivity, Visual Appeal, and Memorable Experience Among Gen Z - Sabila Ulfa Istiqomah; Novel Idris Abas (Universitas Muhammadiyah Surakarta, 2025)
This study aims to examine the influence of interactivity experience and visual appeal on visit intention in virtual cultural tourism, with memorable tourism experience (MTE) as a mediating variable among Generation Z in Indonesia, using the Stimulus-Organism-Response (S-O-R) framework. A quantitative explanatory approach was employed by collecting data from 415 Generation Z respondents who experienced a virtual tour of Borobudur Temple. Data were gathered through an online questionnaire using a five-point Likert scale and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS to test the measurement and structural models. The results indicate that interactivity experience and visual appeal have significant positive effects on memorable tourism experience, while visist intention is significantly influenced by interactivity experience and memorable tourism experience. Visual appeal does not have a direct effect on visit intention but indirectly influences it through memorable tourism experience, confirming the mediating role of MTE. These findings validate the applicability of the S-O-R model in virtual tourism and demonstrate that interactive and emotionally engaging virtual experiences are more effective than visual aesthetics alone in stimulating visit intention. This study offers empirical evidence that enriches virtual tourism literature and provides practical insights for designing technology-based cultural tourism strategies that are more aligned with the characteristics of Generation Z and supportive of cultural heritage promotion.